Analisis Sentimen Film Dirty Vote Menggunakan BERT (Bidirectional Encoder Representations from Transformers) - Sjoraida, Diah Fatma; Guna, Bucky Wibawa Karya; Yudhakusuma, Dudi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research aims to conduct sentiment analysis on reviews of the film